2022
DOI: 10.1002/aenm.202103530
|View full text |Cite
|
Sign up to set email alerts
|

A Single‐Ion Conducting Network as Rationally Coordinating Polymer Electrolyte for Solid‐State Li Metal Batteries

Abstract: Solid state single‐ion conducting polymer electrolytes (SSPEs) are one of the most promising candidates for long‐life lithium‐metal batteries. However, the traditional polyanion‐type structure of SSPEs inevitably gives rise to insufficient conductivity and inferior mechanical stability, which limits their practical application. Herein, an interpenetrating single‐ion network polymer (PTF‐4EO) is fabricated by crosslinking lithium tetrakis(4‐(chloromethyl)‐2,3,5,6‐tetrafluorophenyl)borate salt with tetraethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…EIS plots of the (d) Li/PVEC/Li cell with the SIPPI and (e) Li/PVEC/Li cell after cycling at 25 °C. (f) Comparison of cycle life of Li/Li symmetric cells in this work with the previously reported polymer electrolytes. ,,,,,,, …”
Section: Resultsmentioning
confidence: 89%
“…EIS plots of the (d) Li/PVEC/Li cell with the SIPPI and (e) Li/PVEC/Li cell after cycling at 25 °C. (f) Comparison of cycle life of Li/Li symmetric cells in this work with the previously reported polymer electrolytes. ,,,,,,, …”
Section: Resultsmentioning
confidence: 89%
“…[22] Recently, Lian et al reported an interpenetrating single-ion polymer electrolyte, fabricated by crosslinking lithium tetrakis(4-(chloromethyl)-2,3,5,6-tetrafluorophenyl) borate salt with tetraethylene glycol, which delivered a high room-temperature conductivity of 3.53 × 10 −4 S cm −1 and an exceptional superior Li-ion transference number of 0.92. [23] The scientific community is very active in finding better electrolytes and balancing safety and performance requirements, which are currently the main hurdles to be conquered to enable the next-generation batteries. Intriguingly, ionic liquids have been extensively applied for a long time, owing to their high electrical conductivity (10 −4 to 10 −2 S cm −1 at 25 °C), wide electrochemical stability window (up to 6 V), high thermal stability (up to 200-300 °C), nonvolatility and nonflammability.…”
Section: Introductionmentioning
confidence: 99%
“…103 Lately, an interpenetrating single-ion polymer electrolyte was prepared via crosslinking lithium tetrakis(4-(chloromethyl)-2,3,5,6-tetrafluorophenyl)borate salt and tetraethyleneglycol, which showed a high conductivity of 3.53 × 10 −4 S cm −1 at room temperature and a high Li-ion-transference number of 0.92. 104…”
Section: Developing New Polymeric Electrolytesmentioning
confidence: 99%
“…103 Lately, an interpenetrating single-ion polymer electrolyte was prepared via crosslinking lithium tetrakis(4-(chloromethyl)-2,3,5,6-tetrafluorophenyl)borate salt and tetraethyleneglycol, which showed a high conductivity of 3.53 Â 10 À4 S cm À1 at room temperature and a high Li-iontransference number of 0.92. 104 Despite these advances, a solid electrolyte that possessing a superior ionic conductivity level of 10 À3 S cm À1 at 25 1C, a large cation transference number over 0.8, and a feasibility of matching simultaneously with metallic Li anodes and intercalation cathodes, has not been achieved yet.…”
Section: Developing New Polymeric Electrolytesmentioning
confidence: 99%